2019
DOI: 10.5539/jas.v11n4p142
|View full text |Cite
|
Sign up to set email alerts
|

Grain Yield and Its Associations With Pre-harvest Sprouting in Wheat

Abstract: This study aimed to evaluate direct and indirect effects of agronomic traits importance on grain yield with focus in pre-harvest sprouting. Experiment was conducted in 2017 crop season, and conducted in a randomized block design, with three replications, with eight wheat cultivars (BRS Sábia, CD 105, CD 1104, CD 1440, Frontana, Jadeíte 11, Mirante and ORS Vintecinco). Grain yield and its components were evaluated, as well as other important traits such as pre-harvest sprouting. Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The plant height showed a strong correlation with kernel weight (0.60), this association suggests that tall plants had greater accumulation of photosynthates for the grains, with a longer reproductive period resulting in higher grain weight (Khan et al, 2013;Rigatti et al, 2019).…”
Section: Resultsmentioning
confidence: 96%
“…The plant height showed a strong correlation with kernel weight (0.60), this association suggests that tall plants had greater accumulation of photosynthates for the grains, with a longer reproductive period resulting in higher grain weight (Khan et al, 2013;Rigatti et al, 2019).…”
Section: Resultsmentioning
confidence: 96%
“…Studies have identified several PHS-tolerant genotypes, including Frontana, RL 4137, and BRS 177 (Andreoli et al 2006);Frontana, Fundacep Cristalino, Fundacep Raízes, BRS Guamirim, TBIO Mestre, and TBIO Alvorada (Nörnberg et al 2015b); Frontana, CD 1440, Quartzo, Jadeíte 11, LG Prisma, LG Oro, ORS Vintecinco, TBIO Iguaçu, TBIO Sinuelo, and TBIO Pioneiro (Guarienti et al 2017); Frontana, CD 1440, and ORS Vintecinco (Rigatti et al 2019); hard white winter wheat 'KS Venada' (Zhang et al 2020); and the red-grained cultivar 'AAC Tenacious' (Dhariwal et al 2021).…”
Section: Introductionmentioning
confidence: 99%